Pseudosaccharin amines as potent and selective KV1.5 blockers. Issue 21 (1st November 2015) - Lloyd, John; Finlay, Heather J.; Kover, Alexander; Johnson, James; Pi, Zulan; Jiang, Ji; Neels, James; Cavallaro, Cullen; Wexler, Ruth; Conder, Mary Lee; Shi, Hong; Li, Danshi; et al.
Graphical abstract Synthesis of pseudosaccharin amines as KV1.5 blockers led to the discovery of potent antagonists such as 17d. These compounds had potent pharmacodynamic activity, however, showed off-target activities such as hemodynamic effects.